Chiral Isotropic Sponge Phase of Hexatic Smectic Layers of Achiral Molecules. Issue 7 (20th December 2013) - Chen, Dong; Shen, Yongqiang; Aguero, Jose; Korblova, Eva; Walba, David M.; Kapernaum, Nadia; Giesselmann, Frank; Watanabe, Junji; Maclennan, Joseph E.; Glaser, Matthew A.; Clark, Noel A.
Abstract Smectic layers of tilted, bent‐core liquid crystals have a tendency to exhibit spontaneous saddle‐splay curvature, a mechanical response that relieves the internal strain of the layers. When this tendency is strong enough, the smectic layers form complex, equilibrium, non‐planar structures such as the helical nanofilaments in the B4 phase and the disordered focal conics in the chiral dark conglomerate (DC) phase. The DC phase is usually observed on cooling directly from the isotropic phase, with the disordered focal conics analogous to the disordered sponge phase found in lyotropic systems. We report a DC phase observed below a B2 phase that is stable down to room temperature. In mixtures with the calamitic liquid crystal 8CB, the low‐temperature DC phase forms a more ordered, bicontinuous structure, resembling the cubic phase observed in the lyotropic systems, which is attributed to the enhanced intralayer ordering of the bent‐core molecules in the mixtures.